Exploratory Analysis of Agricultural Indices, Food Imports, and Achievement of Food Security Indicators by Income Level: Selected Asian and Australian Countries - Zainuddin (Universitas Muhammadiyah Yogyakarta, 2025)
Food insecurity, malnutrition, and hunger persist as unresolved issues in many countries in Central, South, Southeast, and East Asia. Importing food as well as focusing on food production can enhance food security in various countries within the area, which is linked to different income levels and other influencing factors. This research examined the effectiveness of agricultural indices, food imports, and seven food security indicators across 23 selected nations in Asia and Australia, categorized by income groups: lower middle, upper middle, and high income. A descriptive method was adopted to examine the non-parametric relationships between variables, elucidated using Biplot diagrams and ultimately displaying the analysis findings using PCA. The findings disclosed a clear link between agricultural indices (agricultural GDP and agricultural public finance) and food supply from imports concerning food security achievements in Asian and Australian countries. Lower-middle-income countries in Southeast, South, and Central Asia exhibited insufficient agricultural output to meet the food needs of their populations. Nevertheless, some of these countries imported a significant amount of food. However, malnutrition, food insecurity, and health problems caused by insufficient food supply and poor nutrition remained significant challenges. Conversely, countries with greater income levels (high and upper-middle) often provided their citizens with improved access to nutritious and high-quality food, fulfilling the energy demands essential for maintaining a healthy and active lifestyle.